Trends in Cesarean Delivery Rates in China, 2008-2018 - Li, Hong-tian (JAMA, 2020)
This study uses China’s National Maternal and Child Health Statistics data set to characterize trends in cesarean delivery rates overall and by urban and rural areas in China between 2008 and 2018.